Willem Janszoon Blaeu, 1571-1638 - Stevenson, Edward Luther, 1858-1944 (Salt Lake City, UT : Project Gutenberg, 2025)
"Willem Janszoon Blaeu, 1571-1638: A Sketch of His Life and Work" by Edward Luther Stevenson, Ph.D. is a historical account written in the early 20th century. The work centers on the life and contributions of Willem Janszoon Blaeu, a prominent cartographer, printer, and globe maker of the early 17th century from the Netherlands. The book delves into Blaeu's significant achievements in the fields of geography and astronomy, particularly noting his famous world map of 1605. The opening of this account introduces readers to Blaeu's early life, beginning with his childhood in Alkmaar and subsequent move to Amsterdam, where he developed a passion for mathematics and astronomy. It highlights his apprenticeship under Tycho Brahe at the observatory on the island of Hveen, detailing his formative years in the realm of scientific study. As the text progresses, it hints at Blaeu's evolution into one of the foremost figures in cartography, setting the stage for exploring his innovations in map-making and printing that would leave a lasting legacy in the scientific community. (This is an automatically generated summary.)
Release date is 2025-02-01
Alan, deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Early maps; Blaeu, Willem Janszoon, 1571-1638